Daniel Breckenridge: capstone - Breckenridge, Daniel, artist (Colorado State University. Libraries, 2018)
The artist's statement: I started my art education aiming to be a photographer. Since a college education is not required for many photographer positions, Ishifted to graphic design. I see graphic design as a branch of marketing. Companies have equity in images. My quality graphic design will translateto company value and project an image the company wants. I aim to create quality visual works within the constraints of capitalism.Computer programs made by Adobe limits refinement and takes away the potential for subtlety in visual work. Having a processed andrefined idea before using a computer can reduce the homogeneity of computer generated art. Adobe has a monopoly on graphic design; butcutting this program out as much as possible will bring fresh work. I hope that my work will be recognized unique with value added through my photographic know how.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design